The impact of social protection and poverty elimination on global tuberculosis incidence: a statistical modelling analysis of Sustainable Development Goal 1 - Daniel J Carter, MSc; Philippe Glaziou, MD; Knut Lönnroth, ProfMD; Andrew Siroka, PhD; Katherine Floyd, PhD; Diana Weil, MSc; Mario Raviglione, ProfMD; Rein M G J Houben, PhD; Delia Boccia, PhD (Elsevier, 2018)
Summary: Background: The End TB Strategy and the Sustainable Development Goals (SDGs) are intimately linked by their common targets and approaches. SDG 1 aims to end extreme poverty and expand social protection coverage by 2030. Achievement of SDG 1 is likely to affect the tuberculosis epidemic through a range of pathways. We estimate the reduction in global tuberculosis incidence that could be obtained by reaching SDG 1. Methods: We developed a conceptual framework linking key indicators of SDG 1 progress to tuberculosis incidence via well described risk factor pathways and populated it with data from the SDG data repository and the WHO tuberculosis database for 192 countries. Correlations and mediation analyses informed the strength of the association between the SDG 1 subtargets and tuberculosis incidence, resulting in a simplified framework for modelling. The simplified framework linked key indicators for SDG 1 directly to tuberculosis incidence. We applied an exponential decay model based on linear associations between SDG 1 indicators and tuberculosis incidence to estimate tuberculosis incidence in 2035. Findings: Ending extreme poverty resulted in a reduction in global incidence of tuberculosis of 33·4% (95% credible interval 15·5-44·5) by 2035 and expanding social protection coverage resulted in a reduction in incidence of 76·1% (45·2-89·9) by 2035; both pathways together resulted in a reduction in incidence of 84·3% (54·7-94·9). Interpretation: Full achievement of SDG 1 could have a substantial effect on the global burden of tuberculosis. Cross-sectoral approaches that promote poverty reduction and social protection expansion will be crucial complements to health interventions, accelerating progress towards the End TB targets. Funding: World Health Organization.